ANALISIS PERBEDAAN KONSEP FITRAH DENGAN NATIVISME, EMPIRISME, DAN KONVERGENSI - As'adatun Niswah; Sriyono Fauzi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Islamic education views fitrah as the primary foundation for shaping a person’s character. This fitrah encompasses various elements, such as the desire to know God and to worship Him. The core objective of this article is to explore these profound differences in order to establish an educational paradigm that is appropriate, balanced, and respectful of humanity. The method used is library research, utilizing existing sources such as books, journals, encyclopedias, papers, articles, and documents. The research findings indicate that the concept of fitrah in Islam is related to the theories of nativism, empiricism, and convergence in explaining human development. Nativism emphasizes innate factors present from birth, empiricism focuses on environmental influences, while convergence combines both factors. The concept of fitrah acknowledges the existence of human potential as well as the importance of the role of the environment and education in developing that potential. However, fitrah has a broader scope because it also considers freedom of choice, individual effort, moral responsibility, and Allah’s guidance. Thus, the concept of fitrah provides a more complete and comprehensive understanding of the formation of human personality from an Islamic educational perspective.